Optical amplifier with flat-gain and wideband operation utilizing highly concentrated erbium-doped fibers - Hamida, Belal Ahmed; Cheng, X. S.; Naji, Ahmed Wathik; Ahmad, Harith; Al-Khateeb, Wajdi Fawzi Mohammed; Khan, Sheroz; Harun, Sulaiman Wadi (World Scientific Publishing Co Pte Ltd, 2012)
In this paper, we proposed a flat-gain and wide-band erbium doped fiber amplifier (EDFA) using two chirped fiber Bragg grating (CFBG) in serial configuration for double-pass operation. The amplifier consists of two sections of Erbium-doped fiber (EDF) operating in C-band and L-band respectively. A CFBG is used in each section to reflect the amplified signal back to the active area so that the overall gain spectrum can be enhanced and flattened. It is also observed that the gain of the amplifier produces a relatively higher gain with the Bismuth-based EDF (Bi-EDF) in the first stage compared to that of silica-based EDF (Si-EDF), especially in a longer wavelength region. The small signal gain of more than 19 dB is obtained within a wavelength region from 1545 to 1605 nm by the use of Bi-EDF with a small noise figure penalty. With a Si-EDF, the flat gain spectrum is observed within a wavelength region ranging from 1535 nm to 1605 nm with a gain variation of less than 2 dB at input signal of 0 dBm. This shows that the proposed serial double-pass amplifier may find its broad applications in wavelength division multiplexing long-haul systems as well as local optical networks.